2006
DOI: 10.1097/01.mlg.0000230402.66579.07
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Endoscopic Cultures on Care in Rhinosinusitis

Abstract: EGCR directed a change in therapy in 35 of 68 (51.4%) patients with CRS. The pathogens isolated from CRS and AECRS were similar and predominately S. aureus, acute pathogens, and P. aeruginosa. Purulent secretions are more frequently bacteriologically positive than nonpurulent secretions and more common in AECRS than CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 14 publications
3
29
1
6
Order By: Relevance
“…The disparity between the available evidence base and existing clinical practice served as an important impetus for the current series. The preponderance of S. aureus and P. aeruginosa in this series has been observed in previous series [5,10]. Cincik and Ferguson noted prevalence of S. aureus and P. aeruginosa in 33% and 18.5% of patients presenting with acute exacerbation of CRS [5].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The disparity between the available evidence base and existing clinical practice served as an important impetus for the current series. The preponderance of S. aureus and P. aeruginosa in this series has been observed in previous series [5,10]. Cincik and Ferguson noted prevalence of S. aureus and P. aeruginosa in 33% and 18.5% of patients presenting with acute exacerbation of CRS [5].…”
Section: Discussionmentioning
confidence: 55%
“…The microbiology of CRS, especially in the post-sinus surgery setting can be quite disparate, with frequent presence of Staphylococcus aureus, coagulase negative Staphylococcus (CNS), and gram negative rods [4]. Thus, endoscopically guided cultures (EGC) are commonly used to guide antimicrobial therapy, with one previous study noting EGCs resulting in change in antibiotic choice in 51.4% of cases [5]. However, there is a paucity of data addressing the essential question if antibiotics derived from EGCs impact objective symptom scores.…”
Section: Introductionmentioning
confidence: 98%
“…The use of culture-directed therapy through endoscopically guided cultures has been emphasized in treatment guidelines and by various authors to help prevent the development of these resistance patterns; however, the theoretical benefi t and importance of this approach remains to be proven [ 34 , 35 ]. One study found that endoscopically guided cultures changed the initial antibiotic management in over one-half of patients, but clinical effi cacy could not be demonstrated [ 36 ]. It follows that culture-directed therapy is a reasonable approach that could aid in more targeted therapy, resulting in less resistance and improved outcomes.…”
Section: Development Of Resistancementioning
confidence: 94%
“…Bhattacharyya and Kepnes [21] recently demonstrated in a multiyear study of 90 adult patients with serial cultures for their acute bacterial exacerbations that using culture-directed therapy for these exacerbations may prevent development of bacterial resistance in individual patients. Cincik and Ferguson [22] also demonstrated that culture-directed therapy changed subsequent antimicrobial management in 51.4% of their patients.…”
Section: Oral Agentsmentioning
confidence: 94%